Hubungan antara Entrepreneurial Orientation dan Creative Self-Efficacy dengan Keunggulan Bersaing pada Content Creator Shopee Affiliate di Bintang Agency Mediatama - Cholid, Ahmad Jauhari; Nuradina, Kartika (Dinasti Research, 2025)
This study explores the relationship between Entrepreneurial Orientation (EO) and Creative Self-Efficacy (CSE) with competitive advantage among content creators participating in the Shopee Affiliate program at Bintang Agency Mediatama. Utilizing a quantitative approach, the research involved 342 respondents and applied multiple linear regression for analysis. The results revealed a significant relationship between EO and CSE with competitive advantage, accounting for 27.1% of the variance. Individually, CSE demonstrated a stronger contribution than EO. These findings emphasize the psychological role of creative self-efficacy in fostering entrepreneurial behavior that supports a strong competitive position. Thus, eìnhancing both EO and CSE is essential to strengthen the creator’s competitiveness in an evolving digital landscape.